The Thermal Decomposition Behavior of Pyrite-Pyrrhotite Mixtures in Nitrogen Atmosphere. (31st January 2022) - Tian, Changshun; Rao, Yunzhang; Su, Gang; Huang, Tao; Xiang, Cairong
Abstract : To assess the thermal transformation process of common sulfide minerals in a nitrogen atmosphere, thermogravimetric analysis, X-ray diffraction, scanning electron microscopy, and thermogravimetric mass spectrometry are employed to define the influence of the pyrrhotite content in pyrite-pyrrhotite mixtures (mixed minerals). The results indicate that an increase in pyrrhotite content decreases the temperature of the maximum mass loss rate of mixed minerals and reduces its mass loss. The solid-phase transformation of the thermal decomposition of mixed minerals is accelerated because the apparent activation energy of pyrrhotite is lower than that of pyrite and mixed minerals. However, the pyrrhotite makes the mixed minerals easier to sinter and agglomerate, which reduces the total volatilization amount of the gas product, S2 ; thus, the rate of mass loss decreases.